Improving the positive predictive value of exercise testing in women. Issue 12 (14th November 2003) - Wong, Y K; Dawkins, S; Grimes, R; Smith, F; Dawkins, K D; Simpson, I A
Abstract : Objective: To identify exercise test variables that can improve the positive predictive value of exercise testing in women. Design: Cohort study. Setting: Regional cardiothoracic centre. Subjects: 1286 women and 1801 men referred by primary care physicians to a rapid access chest pain clinic, of whom 160 women and 406 men had ST depression of at least 1 mm during exercise testing. The results for 136 women and 124 men with positive exercise tests were analysed. Main outcome measures: The proportion of women with a positive exercise test who could be identified as being at low risk for prognostic coronary heart disease and the resulting improvement in the positive predictive value. Results: Independently of age, an exercise time of more than six minutes, a maximum heart rate of more than 150 beats/min, and an ST recovery time of less than one minute were the variables that best identified women at low risk. One to three of these variables identified between 11.8% and 41.2% of women as being at low risk, with a risk for prognostic disease of between 0−11.5%. The positive predictive value for the remaining women was improved from 47.8% up to 61.5%, and the number of normal angiograms was potentially reducible by between 21.1−54.9%. By the same criteria, men had higher risks for prognostic disease. Conclusions: A strategy of discriminating true from false positive exercise tests is worthwhile in women but less successful in men.